Inhibition of rRNA synthesis by poliovirus: specific inactivation of transcription factors. - Rubinstein, S J (1989)
Synthesis of rRNA by RNA polymerase I is almost completely inhibited soon after infection of human cells with poliovirus. We show that extracts prepared from poliovirus-infected HeLa cells are severely inhibited in their ability to transcribe from a human rDNA promoter compared with extracts from mock-infected cells. Two lines of evidence presented here suggest that a specific transcriptional activity required for rDNA transcription in vitro is impaired in virus-infected cells. First, fractionation of individual transcriptional components by phosphocellulose chromatography and subsequent reconstitution experiments showed that the specific transcriptional activity of fraction C (0.8 M KCl eluate) from virus-infected cells was reduced three- to fourfold relative to that isolated from mock-infected cells. The activities of other transcription factors needed for in vitro transcription from the rDNA promoter were unaffected. Second, fraction C derived from mock-infected cells specifically restored transcription in extracts prepared from virus-infected cells. Fraction C contained both a nonspecific RNA polymerase I elongation activity and a specific factor activity which was needed for accurate transcription initiation. It is the specific transcriptional activity and not the nonspecific chain elongation activity of fraction C that is affected in cells infected with poliovirus.